2017
DOI: 10.1111/jfpp.13558
|View full text |Cite
|
Sign up to set email alerts
|

Control ofBacillus cereusspore germination and outgrowth in cooked rice during chilling by nonorganic and organic apple, orange, and potato peel powders

Abstract: The inhibition of Bacillus cereus growth from spores in cooked rice by nine fruit and vegetable peel powders was investigated. The powders were mixed into rice at 10% (wt/wt) along with fourstrain B. cereus cocktail to obtain a spore concentration of about 2.04 log spores per gram. Aliquots (5 g) of cooked rice were cooled from 54.5 to 7.2 8C in 12, 15, 18, or 21 hr, resulting in 1.93, 2.82, 3.83, and 3.58 log cfu/g increases, respectively, in B. cereus levels. Both organic and nonorganic naval orange peel, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…As previously reported [12,14], whole fruits and vegetables, except cherry tomatoes, were individually washed with water, dried with absorbent paper tissue, and manually peeled using a potato peeler. The cherry tomatoes were subjected to blanching before peeling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported [12,14], whole fruits and vegetables, except cherry tomatoes, were individually washed with water, dried with absorbent paper tissue, and manually peeled using a potato peeler. The cherry tomatoes were subjected to blanching before peeling.…”
Section: Methodsmentioning
confidence: 99%
“…We are also engaged in a parallel effort designed to define the potential health benefits of antioxidative fruits and vegetable peels, as well the peel (hull) from rice, which are often discarded as a food-processing waste product [9,10,11]. As part of this effort, we have shown that (a) the dietary supplementation of potato peel powders reduced weight gain in mice on a high-fat diet [12]; (b) potato peel powders inhibited the growth of pathogenic trichomonads (protozoa) that cause sexually transmitted diseases in humans and cattle [13]; (c) apple, orange, and potato peel powders inhibited the outgrowth of pathogenic Bacillus cereus bacteria from spores in cooked rice [14]; and (d) a rice hull smoke extract reduced weight gain in mice on a high-fat diet [15]. We also recently determined the content of phenolic and flavonoid compounds and antioxidative activities of 12 melon peel powders [16].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in potato peels arises from the fact that the annual worldwide production of about 1.3 billion tons of food waste includes potato peels, a peeling byproduct of the industrial production of potato fries, chips, and flour. Because potato and other peels derived from fruits and vegetables contain numerous bioactive compounds, they are a useful and inexpensive source for medical and food uses. …”
Section: Introductionmentioning
confidence: 99%
“…Because potato and other peels derived from fruits and vegetables contain numerous bioactive compounds, they are a useful and inexpensive source for medical and food uses. 7−12 As part of a systematic screening of food processing byproducts containing bioactive compounds, and that have been shown to be active against cancer cells 13 and pathogenic microorganisms 12 and to reduce weight gain in mice on a highfat diet, 14 we tested potato peels, a byproduct of the potatoprocessing industry, against the three pathogenic trichomonads mentioned above. Potato peels are a rich source of bioactive compounds, including the glycoalkaloids α-solanine and αchaconine, as well as a number of antioxidative phenolic compounds such as quercetin and chlorogenic and caffeic acids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, purple-fleshed potatoes are rich sources of anthocyanins, and the amounts stored in peels are usually higher than the flesh when both flesh and peels are coloured (Chaves-Silva et al, 2018). Previous studies have highlighted the bioactive potential of potato peel extracts, for instance their antioxidant (Jeddou et al, 2018;Singh et al, 2011;Singh & Rajini, 2004;Yin et al, 2016), anti-inflammatory (Wahyudi, Ramadhan, Wijaya, Ardhani, & Utami, 2020), antimicrobial (Juneja, Friedman, Mohr, Silverman, & Mukhopadhyay, 2018) and anticancer properties (Reddivari, Vanamala, Chintharlapalli, Safe, & Miller, 2007).…”
Section: Introductionmentioning
confidence: 99%